Cell-Contact-Stimulated Formation of Filamentous Appendages by Salmonella typhimurium Does Not Depend on the Type III Secretion System Encoded by Salmonella Pathogenicity Island 1 - Reed, Katharine A. (American Society for Microbiology, 1998)
The formation of filamentous appendages on Salmonella typhimurium has been implicated in the triggering of bacterial entry into host cells (C. C. Ginocchio, S. B. Olmsted, C. L. Wells, and J. E. Galán, Cell 76:717–724, 1994). We have examined the roles of cell contact and Salmonella pathogenicity island 1 (SPI1) in appendage formation by comparing the surface morphologies of a panel of S. typhimurium strains adherent to tissue culture inserts, to cultured epithelial cell lines, and to murine intestine. Scanning electron microscopy revealed short filamentous appendages 30 to 50 nm in diameter and up to 300 nm in length on many wild-type S. typhimurium bacteria adhering to both cultured epithelial cells and to murine Peyer’s patch follicle-associated epithelia. Wild-type S. typhimurium adhering to cell-free culture inserts lacked these filamentous appendages but sometimes exhibited very short appendages which might represent a rudimentary form of the cell contact-stimulated filamentous appendages. Invasion-deficient S. typhimurium strains carrying mutations in components of SPI1 (invA, invG, sspC, and prgH) exhibited filamentous appendages similar to those on wild-type S. typhimurium when adhering to epithelial cells, demonstrating that formation of these appendages is not itself sufficient to trigger bacterial invasion. When adhering to cell-free culture inserts, an S. typhimurium invG mutant differed from its parent strain in that it lacked even the shorter surface appendages, suggesting that SPI1 may be involved in appendage formation in the absence of epithelia. Our data on S. typhimurium strains in the presence of cells provide compelling evidence that SPI1 is not an absolute requirement for the formation of the described filamentous appendages. However, appendage formation is controlled by PhoP/PhoQ since a PhoP-constitutive mutant very rarely possessed such appendages when adhering to any of the cell types examined.